Rare Variant of GM2 Gangliosidosis through Activator-Protein Deficiency - Brackmann, Florian; Kehrer, Christiane; Kustermann, Wibke; Böhringer, Judith; Krägeloh-Mann, Ingeborg; Trollmann, Regina (Neuropediatrics, 2017)
GM2 gangliosidosis, AB variant, is a very rare form of GM2 gangliosidosis due to a deficiency of GM2 activator protein. We report on two patients with typical clinical features suggestive of GM2 gangliosidosis, but normal results for hexosaminidase A and hexosaminidase B as well as their corresponding genes. Genetic analysis of the gene encoding the activator protein, the GM2A gene, elucidated the cause of the disease, adding a novel mutation to the spectrum of GM2 AB variant. This report points out that in typical clinical constellations with normal enzyme results, genetic diagnostic for activator protein defects should be performed.
Keywords: sphingolipidoses; GM2 gangliosidosis; activator protein; Tay–Sachs' disease